2021
DOI: 10.1051/itmconf/20214003003
|View full text |Cite
|
Sign up to set email alerts
|

Fake News Detection using Machine Learning

Abstract: Everyone depends upon various online resources for news in this modern age, where the internet is pervasive. As the use of social media platforms such as Facebook, Twitter, and others has increased, news spreads quickly among millions of users in a short time. The consequences of Fake news are far-reaching, from swaying election outcomes in favor of certain candidates to creating biased opinions. WhatsApp, Instagram, and many other social media platforms are the main source for spreading fake news. This work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…To contextualize the results obtained, [5] reported an of 85%, precision of 84%, recall of 87%, and F1 score of 85% for their logistic regression classi er. Also, [12] reported an accuracy of 90.32% with SDG and 88.47% and 86.90% with SVM and KNN respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To contextualize the results obtained, [5] reported an of 85%, precision of 84%, recall of 87%, and F1 score of 85% for their logistic regression classi er. Also, [12] reported an accuracy of 90.32% with SDG and 88.47% and 86.90% with SVM and KNN respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Vikram Tembhurne & Almin [14] Kulkarni et al, [5] addressed the concern of fake news in online resources by proposing a machine learning-based detection model. Their study employed classi ers like Random Forest, Logistic Regression, Decision Tree, KNN, and Gradient Booster, the results showed that Logistic Regression achieved the highest accuracy of 85.04%, followed by Random Forest with 84.50% accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical formula y = mx + c is used in linear regression analysis to determine the line of greatest fitting for the correlation between the dependent variable (y) and the independent variable (x) [38]. Gradient Boosting algorithms can optimize different functions, which makes them flexible, and they often provide predictive accuracy [39]. After training and testing the data with the Gradient Boosting model using many cost functions, as shown in Table 7, we got MSE 0.7686.…”
Section: Regression Using Many Functions Of Evaluation Matrixmentioning
confidence: 99%
“…The dynamic system's accuracy is 93%, and it gets better with each repetition. Prasad, Suyash, Rhucha, Prashant and Sumitra in [10] paper, offer a solution by outlining a machine learning-based fake news detection technique. Prerequisite information acquired from different news websites is needed for this model.…”
Section: IImentioning
confidence: 99%